Terrorist financing via the banking sector - Teichmann, Fabian (Crime, law and social change, 2024)
Islamist terrorism poses a significant threat to global security. Current prevention measures focus largely on combating terrorist financing in order to hinder terrorist organizations’ ability to pay their fighters and orchestrate attacks, with the aim of weakening their structures. The banking sector in particular is subject to strict regulations that intend to increase transparency and identify suspicious transactions. However, the present study illustrates that the banking sector continues to offer opportunities for terrorist financing. Using a qualitative study of 15 presumed providers of illegal financial services and 15 compliance experts to detail how terrorist financiers abuse the financial system to fund terrorist organizations, this paper has implications for both compliance officers and regulating authorities. In particular, the perceived challenges facing those at the frontline of the banking sector in detecting and preventing terrorist financing are analyzed with the intention to establish avenues for future research and countering the financing of terrorism regulation.